2002
DOI: 10.1039/b201226j
|View full text |Cite
|
Sign up to set email alerts
|

Rapid separation of pharmaceutical enantiomers using electrokinetic chromatography with a novel chiral microemulsion

Abstract: A novel oil-in-water microemulsion incorporating the chiral surfactant dodecoxycarbonylvaline (DDCV) was used to achieve the rapid enantiomeric separation of pharmaceutical drugs by electrokinetic chromatography (EKC). Incorporation of DDCV into a microemulsion resulted in an elution range more than double that provided the micellar form of the surfactant aggregate. Interestingly, for the same compounds the enantioselectivity provided by the chiral DDCV microemulsions ranged from 1.06-1.30 for the neutral and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 20 publications
0
61
1
Order By: Relevance
“…It was also shown that the presence of 1-butanol (the cosurfactant) was essential -no enantioseparation could be achieved when it was omitted. The second chiral MEEKC separation was reported by Pascoe and Foley [59] in 2002 and utilized a microemulsion based on a chiral surfactant (dodecoxycarbonylvaline, DDCV), an achiral cosurfactant (1-butanol), and an achiral low-interfacial-tension oil (ethyl acetate). Nine pairs of pharmaceutical enantiomers were tested with this chiral surfactant-based PSP and results were compared to those from MEKC using the same chiral surfactant.…”
Section: Microemulsionsmentioning
confidence: 99%
“…It was also shown that the presence of 1-butanol (the cosurfactant) was essential -no enantioseparation could be achieved when it was omitted. The second chiral MEEKC separation was reported by Pascoe and Foley [59] in 2002 and utilized a microemulsion based on a chiral surfactant (dodecoxycarbonylvaline, DDCV), an achiral cosurfactant (1-butanol), and an achiral low-interfacial-tension oil (ethyl acetate). Nine pairs of pharmaceutical enantiomers were tested with this chiral surfactant-based PSP and results were compared to those from MEKC using the same chiral surfactant.…”
Section: Microemulsionsmentioning
confidence: 99%
“…The first publication reported a chiral microemulsion based on a chiral oil, (2R, 3R)-di-n-butyl tartrate, an achiral surfactant (sodium dodecyl sulfate), and an achiral co-surfactant (1-butanol) [11]. In contrast, the latter two publications reported a chiral microemulsion based on a chiral surfactant, dodecoxycarbonylvaline (DDCV), a low interfacial tension, achiral oil (ethyl acetate), 1-butanol as the co-surfactant and a zwitterionic background buffer (ACES) [12,13]. The lack of exploration in chiral MEEKC is surprising for two reasons.…”
Section: Introductionmentioning
confidence: 91%
“…By changing the surfactant concentration, and consequently the aggregate charge density, the elution window can be increased or decreased to optimize retention factors and ultimately resolution. A larger elution range was specifically observed when chiral DDCV MEKC and MEEKC were compared in a previous publication [12], and custom tuning of the elution range has been explored in nonchiral MEKC/MEEKC comparisons [6,14]. Finally, should the area of chiral MEEKC prove successful, the increased solubility range could have wide implications in the chiral analyses of hydrophobic compounds.…”
Section: Introductionmentioning
confidence: 92%
“…High-speed MEEKC using ethyl acetate has been reported [49] which has a lower interfacial tension and requires a lower concentration of SDS to bridge the oil water interface, allowing high voltages to be applied which results in efficient resolution of components. Mertzman [50] and Pascoe [51] have also reported the use of low interfacial oils like ethyl acetate in MEEKC separations. A range of other oils have been reported [26,31,35,37,48,52,53] including cyclohexane, chloroform, methylene chloride, amyl alcohol, and butyl chloride.…”
Section: Oil Phasementioning
confidence: 96%
“…Only in the last four years has there been more work carried out in this area with papers by Pascoe and Foley [51], Mertzman and Foley [15,16,19,21,50], Kahle and Foley [20] and Zheng et al [18]. The chiral surfactant DDCV has been used in a number of applications to achieve enantiomeric separations of a number of pharmaceutical compounds [51].…”
Section: Chiral Separationsmentioning
confidence: 98%